Description of the Basic Technical Skills of Junior Football Players' Passing-Control and Shooting - Andriadi Andriadi; Eka Supriatna; Rubiyatno Rubiyatno; Yohanes Touvan Juni Samodra; Putra Sastaman B (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The ability to take free kicks is owned by every soccer player, as are passing and control abilities. Mastery of these two techniques is very important for a soccer player. This study aims to describe the ability to do free kicks and control passing. The research method used is a survey and is descriptive research. The sample is 15 football athletes at the Mensemat club in Sambar Regency, West Kalimantan. Athletes are given control-passing tests and free calm tests. The data were analysed with descriptive statistics. The results showed that the ability to do free kicks and control passing was still 6% in the bad category; the rest were good or very good. Meanwhile, there are still 13% of free kick abilities in the bad category, and the rest are good or very good.